Tratamento crônico com decanoato de nandrolona prejudica o relaxamento vascular em ratas sedentárias e submetidas a treinamento físico - Caliman, Izabela Facco (2017)
Nandrolone Decanoate (ND) is an Anabolic Androgenic Steroid (AAS) that under abusive regimen can lead to multiple physiological adverse effects. Studies of AASmediated cardiovascular (CV) alterations were mostly taken from male subjects, even though women are also susceptible to the effects of AAS and sex-specific differences in susceptibility to vascular diseases exist. The aim of this study was to investigate NDinduced vascular reactivity alterations in both sedentary and exercised female rats as well as the participation of endothelium-derived factors on the vascular response. Adult Wistar female rats (180-200g), sedentary or exercise trained, intact or ovariectomized, treated with ND (20 mg/kg/week) for 4 weeks were used. At the end of the experimental protocol, dose-response curves to acetylcholine (ACh) were performed in isolated mesenteric vascular beds (MVBs) in the absence and presence of pharmacological inhibitors to assess the vascular reactivity. Our main findings show that chronic exposure of female rats to ND impaired the endothelial function in MVBs from both sedentary and trained animals. The nitric oxide (NO) pathway appear to be the main responsible mechanism involved in the impairment of the vascular reactivity, as observed in the ACh-induced vasodilation in presence of L-NAME (NO synthase inhibitor (NOS) and aminoguanidine (selective inhibitor of inducible NOS), as well as by the decreasing of the phosphorylation sites of eNOS (Ser1177) and Akt (Ser473) and upregulation of iNOS and NADPH oxidase expression. Neither the endotheliumderived hyperpolarizing factor (EDHF) component nor prostanoids were altered in the MVBs from ND-treated females, since in the presence of L-NAME and Indomethacin (cyclooxygenase inhibitor) the vasodilator response to ACh remained unchanged amongst the studied groups.